PENGARUH INTERVAL TRAINING TERHADAP VO2MAX CLUB GULAT PGSI KARO - Janwar Frihasan S Sinuraya; Julius Boy Nesra Basgimata Barus; Eduwaret Pratama Surbakti (JURNAL CURERE, 2023)
Endurance is very important when doing sports, especially for an athlete to be able to maximize when doing a match. Good endurance will see the condition of the body that is able to move without experiencing fatigue, so it is necessary to conduct a study for this research location. The purpose of this study was to determine the effect of interval training on increasing VO2max and the effect of interval training on increasing VO2Max at Karo PGSI Wrestling Club. The method used in this study is the pre-experimental method with interval training exercises. The research design that will be used in this study is the pre-test post-test group design. With the subject The subjects in this study were 10 athletes wrestling PGSI Karo SMK 1 Kabanjahe. The results showed that the average (mean) and VO2max of each of the pre-test data were the lowest, namely 32.8 and the highest, namely 40.5. Then the data obtained by the post-test is the lowest value, namely 40.1 and the highest, namely 44.5. While the pre-test mean value is 36.4 and the post-test mean value is 38.9. Standard deviation (SD) pretest 3.28 and posttest 2.76 and change value (D) 36.4. So it can be concluded that there is a significant effect between interval training on the VO2max of PGSI Karo wrestling athletes by 6.5%.